BUDAYA PEDULI DAN BUDAYA MUTU MELAYANI DI PERPUSTAKAAN SMP NEGERI 13 SURAKARTA MENUJU SEKOLAH MENYENANGKAN - Ria Widyawati (Central Library of Universitas Sebelas Maret, 2016)
Students of SMP Negeri 13 Surakarta mostly students from families with lowereconomic level. Most students of SMP Negeri 13 Surakarta not yet have adequate facilities for the needs of their schools at home, for example a computer or netbook, books that support learning in schools, and other school supplies. Existing facilities at the school became one of the alternatives that can help students to improve students’ quality of human resources. Library SMP Negeri 13 Surakarta has the facilities and infrastructure that can help the students to follow the teaching and learning process in schools. Concern antarsiswa and concerns of the student teachers are needed in the environment of SMP Negeri 13 Surakarta because a lot of students that should beredirected in order to achieve future aspired. Library SMP Negeri 13 Surakarta also constantly improve the quality of services that the students and teachers as library members feel comfortable using the library of SMP Negeri 13 Surakarta. Quality culture serves in the library of SMP Negeri 13 Surakarta realized by improving the quality of services to library patrons, for example the use of an application library to replace the use of the manual on the process of borrowing and returning books as well as data members of the library, so as to realize the school a fun and students can enjoy the learning process, feel comfortable in the environment of SMP Negeri 13 Surakarta,especially if students are in the library.